To Compare The Outcome Of Minor Anorectal Surgeries Under Local Anaesthesia Versus Spinal Anaesthesia - NAGARAJ BHALKI; BALARAJU T C; VINAYAK N T; RAJKUMAR P N; SREEKANTHA; SUDHAKAR G K; YOGESH.B (International Journal of Pharma and Bio Sciences, 2012)
Back Ground: Minor anorectal disease constitutes quite large percentage of cases in surgical out patient department (OPD).This study helps to know the effectiveness of local anaesthesia for day care surgery. Study design: comparative study Materials and Methods: A total of 60 patients were randomly selected into group A(local anaesthesia) and group B(spinal anaesthesia) who underwent minor anorectal surgeries. Each patients detailed history, physical examination, operative details, postoperative complications, length of hospital stay, pain scores, analgesic requirements, and patient satisfaction scores were collected. Results: There were 20 female and 40 male in the study. The mean age was39.53 and 43.17 in group A and group B respectively . The main presenting symptom was bleeding in 26.7% and 60%, mucous discharge in 23.3% and 6.7%, and pain 46.7% and 13.3% in group A and group B respectively. Out of the study group 60% patients were on non-vegetarian diet, which shows a significant increase in patients with low fibre diet. This is further emphasized by the fact that 60% of the patients suffer from constipation.Urinary retention was significantly higher in the group receiving spinal anaesthesia (group b). 30% patients in group b and 6.7% in group A had post operative retention. Post operative pain score was measured by a scale from 0-10(0=no pain, 10=severe pain). The mean patient satisfaction score was 9.31(0=poor satisfaction 10=excellent satisfaction).Data about the number of doses of oral/pareneteral analgesics were recorded.patient subjective success was assessed . Hospital stay was significantly decreased in group A( p value 0.02). 93.3% patients in this group were discharged on day 1 whereas 70% of group B were discharged on day 1. There was no mortality, incontinence, faecal urgency, and persistent pain. Conclusion : The current study was aimed to analyse the feasibility and utility of using alternate method of anaesthesia in patients undergoing surgeries for minor anorectal ailments. The results of this study were in accord with the previous studies. The use of local anaesthesia in these surgeries was found to be beneficial in terms of hospital stay, postoperative complications such as urinary retention. The technique had no significant difference in post operative pain, perioperative Complications and patient satisfaction. Hence it can be concluded that local anaesthesia is a safe and advantageous technique in performing minor anorectal surgeries.